Basic Oxygen Furnace steel slag aggregates for phosphorus treatment. Evaluation of its potential use as a substrate in constructed wetlands. (1st February 2016) - Blanco, Ivan; Molle, Pascal; Sáenz de Miera, Luis E.; Ansola, Gemma
Abstract: Basic Oxygen Furnace (BOF) steel slag aggregates from NW Spain were tested in batch and column experiments to evaluate its potential use as a substrate in constructed wetlands (CWs). The objectives of this study were to identify the main P removal mechanisms of BOF steel slag and determine its P removal capacity. Also, the results were used to discuss the suitability of this material as a substrate to be used in CWs. Batch experiments with BOF slag aggregates and increasing initial phosphate concentrations showed phosphate removal efficiencies between 84 and 99% and phosphate removal capacities from 0.12 to 8.78 mg P/g slag. A continuous flow column experiment filled with BOF slag aggregates receiving an influent synthetic solution of 15 mg P/L during 213 days showed a removal efficiency greater than 99% and a phosphate removal capacity of 3.1 mg P/g slag. In both experiments the main P removal mechanism was found to be calcium phosphate precipitation which depends on Ca 2+ and OH − release from the BOF steel slag after dissolution of Ca(OH)2 in water. P saturation of slag was reached within the upper sections of the column which showed phosphate removal capacities between 1.7 and 2.5 mg P/g slag. Once Ca(OH)2 was completely dissolved in these column sections, removal efficiencies declined gradually from 99% until reaching stable outlet concentrations with P removal efficiencies around 7% which depended on influent Ca 2+ for limited continuous calcium phosphate precipitation. Graphical abstract: Highlights: Weathered BOF steel slag P removal capacity tested in batch and column experiments. 3.1 mg P/g slag and 95% P removal efficiency after 213 days of column experiment. Ca(OH)2 solubility controls Ca–P precipitation and P adsorption in vertical column.